Douglas A. Irvin (ed.). Free Trade under Fire. Princeton, NJ: Princeton University Press. 2005. 294 pages. Price not given. (The Pakistan Development Review, 2008)
International trade around the world is growing rapidly and it is very effective in improving the living standards of a nation, but still free trade faces many critics. They complain that free trade causes harmful economic adjustments, for example increase in unemployment through the closing of factories etc. The critic further object that the World Trade Organisation serves the interests of international corporations, undercuts domestic environment regulations, and erodes America’s sovereignty. Why has global trade become so controversial? Does free trade deserve its bad reputations? These are the questions which inspired the writer to work against these problems. In “Free Trade under Fire”, the author discusses the misconceptions that litter the debate over trade and gives the reader a clear understanding of the issues involved. The aim of this book is to determine the effect of economic, political and legal factors on the trade policy of the United State.